The Influence of Mother's Knowledge of Toddler Nutrition on Their Knowledge and Attitudes Towards Stunting - Siagian, Ernawaty; Ramschie, Putri Agape (Universitas Muhammadiyah Surakarta, 2024)
Stunting under five in children is caused by multifactors, namely maternal knowledge of nutrition, nutritional consumption during pregnancy, limited access to services, inadequate access to sanitation and clean water. The impacts of stunting include a decrease in intelligence, vulnerability to diseases, hampering economic growth and work productivity and exacerbating inequality. The aim of this research is to determine the relationship between maternal knowledge of toddler nutrition, maternal knowledge and attitudes towards stunting. This is quantitative research with a cross-sectional approach. Data collection was carried out by giving out a 39-items questionnaire. The research population was mothers of toddlers who were treated at the Bandar Lampung Adventist Hospital. Research sampling was carried out using simple random sampling. Bivariate analysis was performed using a correlation formula, namely Pearson r. Data were analyzed using the chi-square test which was processed using SPSS. The results showed that maternal knowledge of toddler nutrition was related to maternal knowledge about stunting with a significant value of 0.007 (p<0.05). Maternal knowledge of toddler nutrition is related to maternal attitudes of stunting with a significant value of 0.009 (p<0.05).